Body mass index modifies the relationship between γ-H2AX, a DNA damage biomarker, and pathological complete response in triple-negative breast cancer. Issue 1 (December 2017) - Barba, Maddalena; Vici, Patrizia; Pizzuti, Laura; Di Lauro, Luigi; Sergi, Domenico; Di Benedetto, Anna; Ercolani, Cristiana; Sperati, Francesca; Terrenato, Irene; Botti, Claudio; Mentuccia, Lucia; Iezzi, Laura; et al.
Abstract Background Body mass index (BMI) is largely investigated as a prognostic and predictive factor in triple-negative breast cancer (TNBC). Overweight and obesity are linked to a variety of pathways regulating tumor-promoting functions, including the DNA damage response (DDR). The DDR physiologically safeguards genome integrity but, in a neoplastic background, it is aberrantly engaged and protects cancer cells from chemotherapy. We herein verified the role of BMI on a previously assessed association between DDR biomarkers and pathological complete response (pCR) in TNBC patients treated with neoadjuvant chemotherapy (NACT). Methods In this retrospective analysis 54 TNBC patients treated with NACT were included. The relationship between DDR biomarkers, namely phosphorylated H2A Histone Family Member X (γ-H2AX) and phosphorylated checkpoint kinase 1 (pChk1), and pCR was reconsidered in light of BMI data. The Pearson's Chi-squared test of independence (2-tailed) and the Fisher Exact test were employed to assess the relationship between clinical-molecular variables and pCR. Uni- and multivariate logistic regression models were used to identify variables impacting pCR. Internal validation was carried out. Results We observed a significant association between elevated levels of the two DDR biomarkers and pCR in patients with BMI < 25 (p = 0.009 andp = 0.022 for γ-H2AX and pChk1, respectively), but not in their heavier counterpart. Results regarding γ-H2AX were confirmed in uni- and multivariate models and, again, for leaner patients only (γ-H2AXhigh vs γ-H2AXlow : OR 10.83, 95% CI: 1.79–65.55, p = 0.009). The consistency of this finding was confirmed upon internal validation. Conclusions The predictive significance of γ-H2AX varies according to BMI status. Indeed, elevated levels of γ-H2AX seemed associated with lower pCR rate only in leaner patients, whereas differences in pCR rate according to γ-H2AX levels were not appreciable in heavier patients. Larger investigations are warranted concerning the potential role of BMI as effect modifier of the relationship between DDR-related biomarkers and clinical outcomes in TNBC.